Antibacterial and antibiofilm activity of coenzyme Q0 against Vibrio parahaemolyticus. (March 2020) - Zheng, Xiaoying; Guo, Jialu; Rao, Huishan; Guo, Du; Huang, Yixiao; Xu, Yunfeng; Liang, Sen; Xia, Xiaodong; Shi, Chao
Abstract: Coenzyme Q0 (CoQ0) demonstrates antineoplastic and anti-inflammatory properties; however, its antimicrobial and antibiofilm activities against Vibrio parahaemolyticus have not been extensively examined. Thus, the aim of the current study was to investigate the antimicrobial and antibiofilm activities, along with the underlying mechanism, of CoQ0 against V. parahaemolyticus. The minimum inhibitory concentrations (MICs) of CoQ0 against eight V. parahaemolyticus strains ranged from 4 to 16 μg/mL, while V. parahaemolyticus treated with CoQ0 showed a longer lag phase compared with the untreated control. CoQ0 was effective in destroying cell membrane integrity and inducing morphological changes in the cell. In addition, an antibiotic sensitivity assay showed that CoQ0 caused cell damage associated with DNA, RNA, and proteins. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis confirmed the action of CoQ0 on destroying proteins or inhibiting proteins synthesis of V. parahaemolyticus . CoQ0 effectively inactivated V. parahaemolyticus in mature biofilm on stainless steel surfaces and inhibited V. parahaemolyticus in fresh shrimp. These findings suggested that CoQ0 could be used as a natural antimicrobial and antibiofilm agent to control V. parahaemolyticus in the seafood supply chain, thereby preventing seafood-associated infections. Highlights: The antimicrobial and antibiofilm activity of coenzyme Q0 (CoQ0) was investigated. CoQ0 prolonged lag phase, altered cell morphology, and damaged the cell membrane. CoQ0 inactivated V. parahaemolyticus cells in mature biofilm on stainless steel surfaces and in shrimps. CoQ0 shows potential for the control of V. parahaemolyticus .